Empowering Non-English Teachers Through Clil-Based Training: A Community Service Model In Indonesian Elementary School - Tri Achmad Efendi; Wisnu Kristanto; Apsari Fajar Prihantini; Sulistiyani Sulistiyani (Abdimas Pedagogi: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
English has been a crucial skill in the 21st century. Therefore, most of the schools in Indonesia teach English since in the elementary school. However, many of Indonesian elementary schools do not have English teachers, meaning that students are taught by non-English teachers. That fact also happens at MI Mutaalimin. Most of the teachers graduated from PGSD/PGMI, that makes them as generalist teachers who teach all subjects. They lack of training in teaching English. Therefore, this community service was conducted to help teachers teach English effectively through content language integrated learning (CLIL). This community service was aimed to help non-English teachers teach English effectively through CLIL. The program involved three steps: planning, implementation, and evaluation phase. In the first phase, the questionnaire was distributed to identify problem. Next, the implementation phase involved material delivery session, demonstration, practice and discussion. In the last phase, evaluation, the questionnaire was distributed to gain insight of the implementation of this proposed approach in English language teaching at the school under the study. The results showed that teachers gained new insights how to teach English through subject integration. Also, the training promoted the participants’ confidence and readiness to implement CLIL-based lesson enabling them to deliver English lesson more effectively even though they have limited language proficiency.